THE CHALLENGES OF TEACHING EFL FOR ADULTLEARNERS: ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Assapari, M. Mugni (Jurnal Ilmiah Spectral, 2021)
This study was conducted to determine the challenges of teaching EFL for adult learners online learning in UIN Mataram during the covid-19 pandemic. This study used a qualitative method. Data collection instruments are questionnaires and interviews. The findings of this study show that there are challenges for lecturers in teaching EFL for adult learners. In conclusion, this paper has shown so many responses about the challenges experienced by the lecturer, and students while studying online, such as; the positive and negative impact of online learning.